Workplace violence against frontline clinicians in emergency departments during the COVID-19 pandemic - Rui Liu; Yue Li; Ying An; Ling Zhang; Feng-Rong An; Jia Luo; Aiping Wang; Yan-Jie Zhao; Anzhe Yuan; Teris Cheung; Gabor S. Ungvari; Ming-Zhao Qin; et al. (PeerJ, 2021)
Background Frontline clinicians working in emergency departments (ED) were at disportionate risk of workplace violence (WPV). We investigated the prevalence of WPV and its relationship with quality of life (QOL) in this group of health professionals in China during the COVID-19 pandemic. Methods A cross-sectional, online study was conducted. The nine-item Workplace Violence Scale measured WPV. Results A total of 1,103 ED clinicians participated in this study. The overall prevalence of WPV against ED clinicians was 29.2% (95% CI [26.5%-31.9%]). Having family/friends/colleagues infected with COVID-19 (Odds Ratio (OR) = 1.82, P = 0.01), current smoking (OR = 2.98, P < 0.01) and severity of anxiety symptoms (OR = 1.08, P < 0.01) were independently and positively associated with WPV, while working in emergency intensive care units (OR = 0.45, P < 0.01) was negatively associated with WPV. After controlling for covariates, clinicians experiencing WPV had a lower global QOL compared to those without (F(1, 1103) = 10.9,P < 0.01). Conclusions Prevalence of workplace violence against ED clinicians was common in China during the COVID-19 pandemic. Due to the negative impact of WPV on QOL and quality of care, timely preventive measures should be undertaken for ED clinicians.